158k views
4 votes
What’s the answer to this question below. A b c or d

What’s the answer to this question below. A b c or d-example-1

2 Answers

2 votes

Answer:

The right choice is (2) 0

Explanation:

7 ^(3a-3) = 7^(3a-3)

= -3a -3 = 3a -3

= -3a = 3a

-3a -3a = 0

-6a = 0

a= 0

User Alyssa
by
4.6k points
1 vote

Answer:


a=0

Explanation:

The given expression is;


((1)/(7))^(3a+3) =343^(a-1)

This implies that;


7^(-1(3a+3)) =7^(3(a-1))

Equate the exponents;


-1(3a+3) =3(a-1)

Expand;


-3a-3 =3a-3


-3a-3a =-3+3


-6a=0


a=0

User Roshan N
by
5.5k points